Eddy Viscosity in Accelerated and Retarded Cascade-Wake Flows - J.W. Elsner (Engineering Transactions, 1979)
The paper presents the results of both theoretical and experimental analyses of the eddy viscosity evolution behind the row of symmetrical bodies in a cascade flow with a longitudinal pressure gradient having a constant value in a downstream direction. The investigations have proved that eddy viscosity coefficient decreases decidedly with the growth of the coordinate x1. For x1 -> 11 it appears to be the increasing function of the longitudinal pressure gradient.